Modelling and mitigation of specular multipath interference in a dual-frequency phase comparison FMCW radar system - Schonken, Willem Petrus Francois (Stellenbosch : Stellenbosch University, 2017)
Thesis (DEng)--Stellenbosch University, 2017.